Observational Restrictions on Inflationary Universe Models - Øyvind G. Grøn (Fundamental Research and Application of Physical Science Vol. 8, 2023)
The fewer inflationary models that remain after confrontation with observational data, the more we know about the first moment of the universe. In this paper, more than thirty inflationary models are confronted with the recently improved limit on the tensor-to-scalar ratio presented by the Planck team. It is shown that a few more models are falsified due to this sharper restriction. The study also discusses possible consequences of CMB-S4-observations for these inflationary models. The results are summarized in a table which shows that even if all the models that can be tested against the CMB-S4-observational data are falsified, there remain a handful of models that need other tests, for example polarization tests in order to decide whether they are realistic. Also the theoretical foundations of the models must be judged – whether they can be constructed from fundamental physics or have an ad hoc character and contain adjustable arbitrary parameters, are important.